From the Unification Church to the Unification Movement and Back - Bromley, David G. (Nova religio, 2012)
Two widely observed patterns in the development of new religious movements are a gradual organizational and theological settling of the movement and a transition in leadership from the founder/leader(s) to their successors.1 We report here on the confluence of these two developments in Unificationism over the last several years. This report is based on personal interviews over the last two years with a number of Unificationist leaders and members involved in managing organizational changes. Information also has been drawn from public and members-only websites where internal conversations and new policies are available. Two principal changes in Unificationist organization have occurred. First, longstanding tensions between established church and social movement forms of organization are being resolved in favor of the former.2 Second, Reverend Sun Myung Moon had begun passing organizational leadership to several of his children before his death in September 2012. Both these processes have involved considerable turmoil, overlapping and interacting with one another, and they offer a unique opportunity to observe and record the process of simultaneous transformations of organization and leadership.